2013
DOI: 10.1021/ef400257a
|View full text |Cite
|
Sign up to set email alerts
|

Study of Selected Factors Affecting Hydrate-Based Carbon Dioxide Separation from Simulated Fuel Gas in Porous Media

Abstract: Hydrate-based gas separation is one of the potential methods of carbon dioxide capture from fuel gases (CO 2 /H 2 ) for an integrated coal gasification combined cycle (IGCC) power plant. In this study, the influences of selected factors, including porous properties, tetrahydrofuran (THF) concentration, sodium dodecyl sulfate (SDS) concentration, and initial pressure, of the operation system on hydrate phase equilibria, gas consumption, and gas separation are experimentally investigated by a designed orthogonal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
33
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 71 publications
(33 citation statements)
references
References 39 publications
0
33
0
Order By: Relevance
“…FBR can enhance the gas/ liquid contact and has the advantage of eliminating the need for high cost, energy intensive agitation for hydrate formation. Different porous media like silica gel, silica sand, light weight and highly porous foam, metallic packing, and glass beads have been employed as the bed in FBR (Adeyemo et al, 2010;Babu et al, 2013aBabu et al, , 2013bKang et al, 2013;Kumar and Kumar, 2015;Song et al, 2013). Babu et al (Babu et al, 2013a, 2013c) evaluated the performance of silica sand (inter particle pore space) and silica gel (intra particle pore space) as the bed material for CO 2 /H 2 and CO 2 / H 2 /propane system and reported that silica sand performed better.…”
Section: Introductionmentioning
confidence: 99%
“…FBR can enhance the gas/ liquid contact and has the advantage of eliminating the need for high cost, energy intensive agitation for hydrate formation. Different porous media like silica gel, silica sand, light weight and highly porous foam, metallic packing, and glass beads have been employed as the bed in FBR (Adeyemo et al, 2010;Babu et al, 2013aBabu et al, , 2013bKang et al, 2013;Kumar and Kumar, 2015;Song et al, 2013). Babu et al (Babu et al, 2013a, 2013c) evaluated the performance of silica sand (inter particle pore space) and silica gel (intra particle pore space) as the bed material for CO 2 /H 2 and CO 2 / H 2 /propane system and reported that silica sand performed better.…”
Section: Introductionmentioning
confidence: 99%
“…More recently, people have investigated the effects of using novel materials such as polyurethane foam and metallic packing as packing media, on hydrate formation [44,51]. The kinetics of hydrate formation can also be enhanced by the use of surfactants such as Sodium Dodecyl Sulfate (SDS) in small doses of the order of ppm as additives [42,[52][53][54][55][56][57][58][59][60][61].…”
Section: Introductionmentioning
confidence: 99%
“…There are many potential applications based on hydrate, such as separation of gas mixtures. [1][2][3][4][5][6] However, the formation and agglomeration of hydrate can also cause plug in multiphase gas and oil transportation pipeline. 7 The injection of inhibitors is often adopted to solve the hydrate plug problem.…”
Section: Introductionmentioning
confidence: 99%